Utilization of brewer\'s spent yeast as a bio-vehicle for incorporation and protection of bioactive compounds - Rubio, Fernanda Thaís Vieira (2021)
The disposal of wastes and byproducts from agriculture and food industry is undoubtedly of a great concern, especially because these materials could represent valuable sources of bioactive compounds, dietary fibers and nutrients, which can be reused in the production of novel additives or products. In this context, grape pomaces, jabuticaba byproducts, pumpkin peels and yeasts are examples of byproducts that present potential nutritional value and were used in this work. Grape pomaces and byproducts of jabuticaba pulping are rich in phenolic compounds, such as anthocyanins, pumpkin peels represent a carotenoid-rich source and yeasts contain proteins, complex B vitamins and carbohydrates and have been used for food applications. The main objective of this work was taking advantage of the pre-formed capsule morphology of yeasts Saccharomyces cerevisiae to incorporate bioactive compounds using the spray drying technology, associating the nutritional value of yeast with the health-benefit properties of the bioactive compounds. In general, yeast-based microcapsules produced in this work presented low values of water activity, moisture content and hygroscopicity, assuring a physical and microbiological stability for the powders. MIR-ATR analysis showed significant differences between yeasts before and after encapsulation of bioactives, suggesting the yeast loading. Confocal laser scanning microscopy helped to understand the distribution of the bioactives all over the cell after encapsulation, confirming the presence of compounds inside the yeasts. Compounds stability during storage was higher for phenolic compounds in comparison to carotenoids. The release of the compounds incorporated in yeasts was evaluated during an in vitro gastrointestinal digestion and the microparticles released gradually the compounds, protecting them from gastric conditions and releasing them in higher content in the intestinal phase, which has a positive effect for the compounds bioaccessibility. Enriched yeasts were used as potential natural colorant in yogurts and conferred color to the product. Enriched yogurts were well accepted by consumers. In addition to proposing the utilization of industrial byproducts, this work contributes to scientific advances by addressing the use of yeasts as innovative and bio-based vehicles for incorporation of different compounds and approaching new perspectives for enriched yeast utilization.